Pengaruh Budaya Organisasi Clan terhadap Keterlibatan Karyawan di Institusi Pendidikan - Dede Ahmad Sobari; Amedia Puspa (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
Corporate culture is very important to determine employee engagement, especially in educational institutions, where management and employees work together to achieve common goals. The influence of clan-type organizational culture on employee engagement in educational institutions is the subject of this study. It is considered relevant to create a work environment that supports active participation of clan culture employees, which is characterized by the values ​​of family, cooperation, and caring. This quantitative study used a survey as a sample. Data were collected through distributing questionnaires to 75 employees of participating educational institutions. The relationship between variables was examined using simple linear regression data analysis methods. The study showed that clan organizations increase employee participation. Employee engagement is higher in workplaces where there is a strong sense of trust, open communication, and teamwork. This shows how important it is for educational institutions to adopt clan principles to increase employee participation. Ultimately, this will help the organization achieve its goals.